MAT444acm104hw4 - Alex Gittens February 9, 2007 ACM 104: HW...

• Notes
• 7

This preview shows page 1 - 3 out of 7 pages.

The preview shows page 1 - 3 out of 7 pages.
Alex GittensFebruary 9, 2007ACM 104: HW 4Exercise 1.Find the Jordan canonical form and the corresponding Jordan canonical basis for the followinglinear operators.(a)T:R3R3defined byTx=AxforxR3whereA=11-4-521-8-113-10.(b)T:P2(R)P2(R) defined byT(f) = 2f-f.Answer.
2(b) Letβ={1, x, x2}, thenT(1) = 2T(x) = 2x-1T(x2) = 2x2-2x,soA= [T]β=2-1002-2002,soλ= 2 and dim(Kλ) = 3.To find a basis forKλ, first check the dimension of the eigenspace:Ax= 2xx=c100dim(Eλ) = 1.Note a basis ofKλcannot consist of an eigenvector and a two cycle of generalized eigenvectors, becausethe initial vector of the cycle would be an eigenvector, so these three vectors would not be linearlyindependent. Instead, the basis ofKλmust be a three cycle of generalized eigenvectors{(A-2I)2v,(A-2I)v, v}such that the initial vector is an eigenvector:(A-2I)3v= 0v=a001+b010+c100.Takev=001(A-2I)v=0-20,(A-2I)2v=200.Therefore{2,-2x, x2}is a Jordan canonical basis forTandJ=2000-20001-12-1002-20022000-20001=210021002is a Jordan canonical form ofT.

Course Hero member to access this document

Course Hero member to access this document

End of preview. Want to read all 7 pages?

Course Hero member to access this document

Term
Fall
Professor
N/A
Tags
Jordan Canonical Form, Jordan canonical basis, K, K i